Top Global Concrete-Producing Countries: A Hierarchical Cluster Analysis of Concrete Production, CO2 Emissions, and Economic Growth - Hilal, Iin Shabrina; Idroes, Ghalieb Mutig (Heca Sentra Analitika, 2025)
Concrete production plays a vital role in infrastructure and economic development, yet it remains one of the most significant sources of global CO2 emissions. This study focuses on the top 10 concrete-producing countries, using variables such as concrete production (CP), carbon dioxide (CO2) emissions, and gross domestic product (GDP) as a proxy for economic growth. Using hierarchical cluster analysis, we categorize the countries into three distinct groups based on the combined metrics. Cluster 1 includes developing and transitional economies such as India, Indonesia, Brazil, Egypt, Russia, Turkey, and Vietnam, which exhibit moderate levels of CP and GDP alongside relatively low CO2 per capita. Cluster 2, represented by China and Saudi Arabia, demonstrates high levels of CP and CO2, coupled with moderate to high GDP, reflecting intensive industrial activity and rapid development. Cluster 3, which includes only the United States, is characterized by high GDP, moderate CP, and persistently high CO2, indicating a stable developed economy that maintains its prosperity through infrastructure upkeep rather than rapid growth. The findings reveal how these three indicators interact across different stages of development and emphasize the importance of tailored sustainability strategies.